Economic preferences and trade outcomes - Alex Korff; Nico Steffen (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2019)
Utilizing the new Global Preference Survey (GPS) by Falk et al. (2018) and its data of unique scope on national preference structures in patience, risk attitude, reciprocity, trust and altruism, we are the first to explore a potential in uence on international trade outcomes of this broad set of economic and social preferences in a unified setting. Adding to the evidence on preferences' importance for aggregate outcomes, we find distinct relationships between national preference leanings and marked differences in trade ows and relationships, both on the country-level and between bilateral partners. Our main results suggest that countries differing in their willingness to behave negatively reciprocal tend to trade significantly less amongst each other, while countries that are patient or risk-averse tend to shift towards exporting more differentiated goods as opposed to homogeneous goods and vice versa.
Keywords: F10; F14; D01; D91; Z10; 330; Trade determinants; Non-Tari Barriers; Economic preferences; Sociocultural variation